Przyjaźń i wspólnota, jako czynniki autentyzmu życia i działania ludzi. Kilka uwag na podstawie własnego doświadczenia - Sztylka, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2009)
Friendship is the foremost form of human individual relation, a demanding community of ethical courage and reciprocation of the measure of life in the ethico-existential dimension. The said relation is of autotelic nature, being no substitute for other forms of human co-existence, however it contributes to solving issues insurmountable in other forms of human relations. It opens up the human’s existence to wider dimensions of co-existence and cofeeling. In the human community a man’s development – of an individual and that of a member of the society – is determined by their gradual realization of stable humanistic values, constituting the fundamental criterion of their attitude towards reality. The human closeness and reciprocating the measure of life are the basic features of friendship and community. That makes those qualities compatible both existentially and practically. The abovementioned forms of human existence have to be clearly distinguished from the passing conventional reciprocity, founded on the societally-accepted concept of “the idol of the market”. The relevance of the will to authenticity of the co-existing human beings, finding its expression in practicing equivalency in acts of reciprocity and shaping a mutually adequate measure of life, has to be strongly emphasized.